PEMBELAJARAN PAI SEBAGAI SARANA INTEGRASI NILAI-NILAI AGAMA DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI ERA DIGITAL - Amelia, Devi; Ainal Gani; Evi Febriani (Inspiratif Pendidikan, 2026)
This study aims to analyze the implementation of Islamic Religious Education (PAI) learning as a means of integrating religious values ​​in character building for students in the digital era at SMAN 1 Tumijajar, Tulang Bawang Barat. The study used a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing. The results show that the integration of religious values ​​is implemented systematically through learning materials, collaborative methods, the use of digital media (YouTube, Instagram, and TikTok), and the familiarization of school culture through the "Jumat Seroja" program. PAI teachers act as facilitators and role models in internalizing religious values, responsibility, discipline, cooperation, and social awareness. This integration not only touches the cognitive domain, but also the affective and psychomotor domains through habituation and critical reflection on digital phenomena. These findings confirm that adaptive and contextual PAI learning contributes significantly to shaping students' religious character and digital ethics, although its success still requires synergy between schools and families.